2023
DOI: 10.1088/1742-6596/2614/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Foundation Types for Mechanized Construction of 220 kV Overhead Transmission Lines in Mountainous Areas Suitable for Fujian Province

Xiaoyu Huang,
Fenqian Wu,
Shaoyuan Lin
et al.

Abstract: The construction of overhead transmission lines in mountainous areas poses a significant challenge when it comes to foundation construction. The type of foundation selected in these areas has a direct impact on equipment selection and access road planning. Fujian Province, located on the southeastern coast of China, is predominantly hilly and mountainous. Therefore, selecting an appropriate foundation for overhead transmission lines is crucial for successful mechanized construction of transmission lines in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Ning et al [23] showed that red clay has little effect on the mechanical behaviors of rock-similar materials, and the proportion of clay in the aggregate is chosen to be 10%. Equation (1) shows that the four factors can quantitatively describe the mass compositions of rock-similar material. The values of the four factors are selected, as shown in Table 1, using the orthogonal design method.…”
Section: Orthogonal Design Methods Of Rock Similar Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ning et al [23] showed that red clay has little effect on the mechanical behaviors of rock-similar materials, and the proportion of clay in the aggregate is chosen to be 10%. Equation (1) shows that the four factors can quantitatively describe the mass compositions of rock-similar material. The values of the four factors are selected, as shown in Table 1, using the orthogonal design method.…”
Section: Orthogonal Design Methods Of Rock Similar Materialsmentioning
confidence: 99%
“…With the rapid development of China's infrastructure, more and more transmission lines are being built in mountainous and high mountain areas, where the tower foundation plays an important role in the construction of transmission lines due to limited construction space and large-scale construction equipment, such as the anchor foundation [1], conical shell foundations [2]. The digging hold foundations are quite popular for special geological conditions and harsh construction environments due to their high bearing capacity and easy construction, which has been widely applied in mountainous and high mountain areas.…”
Section: Introductionmentioning
confidence: 99%